Period2 is associated with immune cell infiltration and is a potential diagnostic and prognostic marker for hepatocellular carcinoma - Chen, Xiaolin; Zhao, Qiaosu; Wang, Haibiao; Qiu, Kaijie; Deng, Xi; Xu, Feng (Frontiers in Molecular Biosciences, 2023)
Background：Hepatocellular carcinoma (HCC) health challenge worldwide. Many studies showed that circadian rhythms play a critical role in tumor development. This study aimed to investigate the role of the circadian gene period2 (PER2) in HCC development and explore the possible mechanisms involved.Methods：From fresh HCC tissues and paired paracancerous tissues, we measured PER2 mRNA and protein expression levels and calculated the correlations between PER2 expression and clinicopathological parameters in patients with HCC. We used transcriptome data from The Cancer Genome Atlas to mine the PER2 gene, including single gene difference analysis, single gene coexpression analysis, gene set enrichment analysis, immune infiltration analysis, and methylation analysis to explore its role and mechanism in HCC occurrence and development.Results：PER2 expression levels were significantly lower in HCC tissues than in the paired paracancerous tissues. PER2 expression in HCC significantly correlated with neural invasion, Child-Pugh classification, and China liver cancer staging stage in HCC patients. The differentially expressed genes associated with PER2 were significantly enriched in mitochondrial oxidative phosphorylation, transcriptional translation, amino acid metabolism, and other related pathways. PER2 expression levels significantly correlated with immune cell infiltration and immune checkpoint genes and positively correlated with TP53 expression in HCC tissues. The DNA methylation status in eight CpG islands of the PER2 gene was associated with HCC outcomes.Conclusions：PER2 is a potential diagnostic and prognostic biomarker and a promising therapeutic target in HCC.